Pendampingan Screening Kesehatan dan Imunisasi BIAS Siswa SD Negeri Wilayu Kecamatan Selomerto Wonosobo - Ashief El Qorny; Vava Imam Agus Faisal; Zhul Fahmi Hasani; Robingun Suyud El Syam (Jurnal Nusantara Berbakti, 2025)
Health is an important factor in people's lives. In order to realize this, health screening and BIAS immunization are preventive measures against the presence of a disease. The purpose of this community service is to find out how to provide assistance for health screening and BIAS immunization activities at Wilayu Elementary School, Selomerto District, Wonosobo Regency. The empowerment stages go through three steps: preparation, implementation, and evaluation. Qualitative research settings by collecting data through observation, interviews, and documentation. The results of this activity indicate that assistance for health screening and BIAS immunization activities is very beneficial for Wilayu Elementary School students where it can foster awareness of healthy lifestyles in everyday life. This BIAS immunization is given to maintain immunity levels above the protection threshold, and is also part of efforts to prevent and overcome diseases early through School Health Efforts. This contributes to an understanding of the importance of a healthy lifestyle, avoiding attitudes that allow the birth of disease considering its systemic impact on life.